If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8a + -1(4a + -3) = 1 Reorder the terms: 8a + -1(-3 + 4a) = 1 8a + (-3 * -1 + 4a * -1) = 1 8a + (3 + -4a) = 1 Reorder the terms: 3 + 8a + -4a = 1 Combine like terms: 8a + -4a = 4a 3 + 4a = 1 Solving 3 + 4a = 1 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4a = 1 + -3 Combine like terms: 3 + -3 = 0 0 + 4a = 1 + -3 4a = 1 + -3 Combine like terms: 1 + -3 = -2 4a = -2 Divide each side by '4'. a = -0.5 Simplifying a = -0.5
| z/3=-14 | | x^2(x+1)=k^2(x+1) | | z/=-14 | | 25x-5=120 | | -3y^2+13y+10=0 | | -x-8=2+4x | | (y/5)=-5 | | 4-6x=-2x | | 1/5-1/10-1/4 | | A=x+y+2015 | | 1.5x-0.5x=10 | | y=-1/7-4 | | 6=h+35 | | {x/x-2} | | 16x+4=7x | | 2y-1=49 | | Y^2+10y-2y-24=0 | | 15=2y+3 | | 2y-6=28 | | 5/2n-3 | | sqrt(x-8)=5 | | 20x6/5 | | 16(v+1)-4v=3(4v+4)-21 | | 4-2x+4x=26 | | 10=2(x+-1) | | 12x+84=x^2+17x+60 | | 0=x^4-x^3+2x-2 | | 16y=-144+4x | | 32x^5-32x= | | 24y=-120+8x | | m/13-6 | | 5x-(6x-7)=4-3(x-3) |